2013
DOI: 10.1246/cl.130446
|View full text |Cite
|
Sign up to set email alerts
|

Unique Mesoporous Silicoaluminophosphate Assembled from Faujasite-type SAPO-37 Precursor: A Potential Catalyst for Isomerization

Abstract: Unique mesoporous silicoaluminophosphate (MESO-SAPO-37) with uniform pores (3 nm) was synthesized for the first time by using a faujasite-type microporous SAPO-37 precursor. MESO-SAPO-37 contains hierarchical mesopores with a microporous secondary building unit. It possesses strong acidity and shows high catalytic activity for the conversion of 1-octene, with the exclusive formation of isomerized products (84%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…To ascertain that the crystalline, faujasitic structure of SAPO‐37 was retained after dual‐templating, the calcined products were analyzed by powder X‐ray diffraction (XRD). To the best of our knowledge, only one group has reported the synthesis of a hierarchical SAPO‐37 material . Although the authors identified mesoporosity by N 2 gas adsorption and low‐angle XRD, the high‐angle XRD pattern of their MESO‐SAPO‐37 was markedly different from FAU, which suggested that the microporous framework was not crystallized.…”
Section: Resultsmentioning
confidence: 99%
“…To ascertain that the crystalline, faujasitic structure of SAPO‐37 was retained after dual‐templating, the calcined products were analyzed by powder X‐ray diffraction (XRD). To the best of our knowledge, only one group has reported the synthesis of a hierarchical SAPO‐37 material . Although the authors identified mesoporosity by N 2 gas adsorption and low‐angle XRD, the high‐angle XRD pattern of their MESO‐SAPO‐37 was markedly different from FAU, which suggested that the microporous framework was not crystallized.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S2 shows the powder X-ray diffraction patterns of as-prepared diaminosilane functionalized SAPO-37. The diffraction patterns of all the samples (SAPO-37-DAS-0.04 to SAPO-37-DAS-0.32) exhibited characteristic reflections corresponding to the SAPO-37 framework 33 34 35 . The XRD patterns remained intact with a highly crystalline phase even in the presence of large amount of diaminosilane functionality introduced, suggesting that the faujasite-type SAPO-37 framework structure was preserved during synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…This study clearly shows that sodium nitrate extraction method efficiently removes the template from diaminosilane functionalized SAPO-37. The extraction method have been extended to MESO-SAPO-37 (as shown in Figure S6 ) prepared as per the procedure described earlier 34 35 , and other microporous systems viz. SAPO-40, SAPO-5 (as shown in Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, its application prospect and future development in modern petrochemical industry are restrained greatly [16], especially for the conversion of large molecules as those encountered in heavy crude oil catalytic cracking process [17,18]. In order to overcome limitations of single microporous or mesoporous molecular sieves and to make preponderance complementarity between the two type molecular sieves, some research groups had extended new synthesis strategy to prepare mesoporous SAPO [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%